Decision support strategies for bedside nursing clinical reasoning: A scoping review protocol (Research, Society and Development, 2024)
The aim of this scoping review is to map the evidence on self-instructed bedside decision strategies applied by nurses to support clinical reasoning. The ability to perform solid clinical reasoning is essential for providing healthcare with favourable patient outcomes. Accordingly, nurses should play an active role in developing clinical reasoning skills. Bedside support strategies are intended to be pragmatic, invaluable, and easy-to-apply resources to restructure cognitive processes when the clinical demands are complex. This review will consider studies that focus on bedside decision strategies, context-suitable, and practical to apply, self-instructed by nurses aimed to support nursing clinical reasoning. Studies focused on educational content, clinical case-specific studies, and studies related to software applications development or artificial intelligence will be excluded. The methodology will follow the JBI recommendations for scoping reviews. All published and unpublished sources of relevant evidence will be considered. Studies published in Portuguese, English, Spanish or Swedish will be included, without geographical or cultural limitations. Duplicates will be removed, and two independent reviewers will screen the abstracts and appraise the full text of the selected studies, based on the inclusion criteria. The results of the study selection will be summarized in a flowchart adapted from Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). The overview of datasets will be presented in a narrative summary to provide a description of the existing evidence.